Stunning : a pretty little liars novel - Shepard, Sara, 1977- (New York : HarperTeen, 2012)
Struggling to return to normalcy after surviving Alison's attempt to kill them, Spencer, Aria, Emily and Hanna endure a series of disasters before realizing that they are being stalked by a new "A" who knows all of their secrets.
Keywords: Teenage girls -- Juvenile fiction; Friendship -- Juvenile fiction; Secrecy -- Juvenile fiction; Conduct of life -- Juvenile fiction; High schools -- Juvenile fiction; Mystery and detective stories